Pengaruh Dewan Komisaris Dan Komite Audit Terhadap Kualitas Laporan Keuangan - Imron Ritonga, Muhammad; Ermian Challen, Auliffi; Ritonga, Pardomuan (GEMA EKONOMI, 2023)
This study aims to examine the effect of the board of commissioners as measured by the size of the board of commissioners and independent commissioners and the audit committee as measured by the size of the audit committee, audit committee meetings, and audit committee expertise on the quality of financial statements partially. The research method used is quantitative research method, using secondary data, namely manufacturing companies listed on the Indonesia Stock Exchange for the period 2017-2021. The sample used was 22 companies. The method used is purposive sampling method. The analysis method used is multiple linear regression analysis with a significant level of 5%. The results of this study indicate that the size of the board of commissioners has no effect on the quality of financial statements, independent commissioners have no effect on the quality of financial statements, the size of the audit committee has a positive effect on the quality of financial statements, audit committee meetings have no effect on the quality of financial statements, and audit committee expertise has no effect on the quality of financial statements.